CHANGES IN THE CONSTITUTIONAL POSITION OF THE PUBLIC PROSECUTOR’S OFFICE IN THE CONSTITUTIONAL REVISION 2022: 1. УВОД, 2. ИЗМЕНЕ ПОЛОЖАЈА ЈАВНОГ ТУЖИЛАШТВА И СПОЉНА И УНУТРАШЊА ОДГОВОРНОСТ, 3. ПОЧЕТАК И ПРЕСТАНАК ЈАВНОТУЖИЛАЧКЕ ФУНКЦИЈЕ, СТАТУС, 4. НОВИ ВИСОКИ САВЕТ ТУЖИЛАШТВА, 5. ЗАКЉУЧАК - Orlović, Slobodan Petar; Rajić, Nataša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
Summary: The paper critically analyzes the provisions of the amendments of the Constitution adopted in 2022, regarding the change of the position of the public prosecutor’s office. The third initiative for the partial change of the Constitution was fruitful. The provisions which regulate the constitutional position of judiciary and prosecutor’s office were changed, with the initial aim to create the independence guarantees of the judiciary, as well as the autonomy of the prosecutor’s office. Certain steps that would go in the direction of achieving the given aim, can be recognized in the norms of the amendments. Those amendments have been also confirmed by the Venice Commission, which are considered as the key factor. However, the first impression created by the amendment provisions is that they are the result of a compromise and therefore partly inconsistent, between: the initiator of constitutional amendments (Government), representatives of the court’s and the prosecutor’s associations, other members of the working group, and, lastly, international community. Within that impression, the new position of the public prosecutor’s office primarily indicates that the prosecutor’s office rose to the rank which the judicial branch of power enjoys, by copying the provisions of the judiciary, with only a few differences.